Venice's hidden enemies : Italian heretics in a Renaissance city - Martin, John Jeffries, 1951- (Berkeley : University of California Press, 1993)
How could early modern Venice, a city renowned for its political freedom and social harmony, also have become a center of religious dissent and inquisitorial repression? To answer this question, John Martin develops an innovative approach that deftly connects social and cultural history. The result is a profoundly important contribution to Renaissance and Reformation studies. Martin offers a vivid re-creation of the social and cultural worlds of the Venetian heretics--those men and women who articulated their hopes for religious and political reform and whose ideologies ranged from evangelical to anabaptist and even millenarian positions. In exploring the connections between religious beliefs and social experience, he weaves a rich tapestry of Renaissance urban life that is sure to intrigue all those involved in anthropological, religious, and historical studies--students and scholars alike.
Front matter -- Contents -- Preface -- Introduction: Salvation and Society in Sixteenth- Century Venice -- 1. A Republic Between Renaissance and Reform -- 2. The Coming of the Inquisition -- 3. Evangelism and the Emergence of Popular Reform -- 4. The Humanity of Christ and the Hope for the Messiah -- 5. Hiding -- 6. The Place of Heresy in a Hierarchical Society -- 7. The Turn of the Screw -- 8. Two Horsemen of the Apocalypse -- Epilogue: The Final Executions -- Appendix: A Note on the Quantitative Study of the Inquisition -- Sources and Bibliography: Heresy and Reform in Sixteenth-Century Italy -- General Index -- Index of Secondary Authors
Based on the author's thesis (doctoral)--Harvard University.
Includes bibliographical references (pages 249-271) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Christian heresies -- Italy -- Venice -- History -- 16th century; Renaissance -- Italy -- Venice; Reformation -- Italy -- Venice; Venice (Italy) -- Church history; Venice (Italy) -- Intellectual life; Venice (Italy) -- History -- 1508-1797.; Hérésies chrétiennes -- Italie -- Venise -- Histoire -- 16e siècle.; Renaissance -- Italie -- Venise; Réforme (Christianisme) -- Italie -- Venise; Venise (Italie) -- Histoire -- 1508-1797.; RELIGION -- History; HISTORY / Europe / General; Christian heresies; Intellectual life; Reformation; Renaissance; Italy -- Venice; 1500-1797; Heresies -- History; Venice (Italy); Church history; History